When Grief Arrives: An oral history of grief and death within queer, trans and Black, Indigenous and people of colour communities - Anne-lise Ah-fat (International Journal of Narrative Therapy and Community Work, 2024)
When Grief Arrives is a narrative therapy and oral history project aimed at re-storying narratives of grief and loss within queer, trans and Black, Indigenous and people of colour communities. The project documents multi-storied accounts of grief that resist the individualisation and isolation of grieving that is common under settler colonialism and capitalism. By honouring overlooked landscapes of experience, the project seeks to generate solidarity and interconnection through shared knowledges. This article discusses the project’s methodology, ethical considerations, and the transformative potential of collective storytelling in fostering solidarity and healing within marginalised communities.